Implementation of Digital Story Telling (DST) Strategy in Arabic Learning (Case Study at Arrifaie Gondanglegi Middle School Malang) - Burhan Lukman Syah; Muhammad Safari; Reiza Aufa Ulwan (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
Today technology is growing rapidly. This makes us (humans) become digital natives so not only adults but teenagers have now spread to consume technology, especially social media. The world of video editing is no longer a stranger to teenagers, especially the students of Al-Rifa'ie Gondanglegi Modern Junior High School Malang. So in this case the researcher implements a learning strategy that combines maharah al-kalam learning with today's technological advances, namely digital storytelling (DST). This strategy makes students want to practice maharah al-kalam but in a more contemporary way, which is packaged via video. The purpose of this research is to find out the application of digital storytelling strategy (DST) in learning maharah al-kalam and also to know some problems in its application. The research method used in this research is descriptive qualitative. The results of the research are that this method is a method that combines many student skills ranging from speaking skills, writing skills, presentation skills (performing) and skills in using technology. And the problem that occurs when learning is the lack of students' mastery of Arabic vocabulary so that in the preparation of the script it is a bit hampered and the limited use of laptop / cellphone media because the majority of students are students who live in Islamic boarding schools so that the time in the video editing process is a bit long. The advantages of this strategy are that it is interesting to use in a variety of student learning styles, arouses student interest, attention and motivation in the classroom, makes digital storytelling (DST) based on students' own creative talents, digital storytelling (DST) as a tool to create a creative learning and can increase students' self-confidence.